STUDI PENILAIAN KINERJA DOSEN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI PERGURUAN TINGGI - Usman; Naim, Suaidin (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2025)
This research aims to explain in detail the dimensions and indicators of lecturer performance and analyze how lecturer performance indicators influence the quality of teaching in higher education. This research used qualitative methods, and obtained a conclusion that lecturer performance, which includes lecturers' work in all aspects of educational management, such as designing and conducting the lecture process, assessing learning outcomes, guiding students, and fulfilling teaching duties. A lecturer's performance depends not only on his or her academic background but also on the application of the required skills. Improving the quality of education is a national strategic issue and is the focus of education quality management research. Lecturer performance is a very important factor that can influence the efficiency of higher education in achieving set educational standards. Teacher expertise and personality have a significant influence on achieving quality standards in higher education teaching. Research findings confirm that good lecturer performance and adequate academic background can influence the overall quality of education. Thus, the positive impact of lecturer performance and academic qualifications is an important variable in efforts to improve the quality of education.